Trial Production and Testing of cement-bonded particles board from rattan furniture waste (2002)
An investigation was conducted on the use of rattan (cane) furniture waste as furnish material for the manufacture of cement-bonded particleboard (CBP). Laboratory scale CBPs were fabricated from hot water pretreated chopped strands of mixed rattan waste obtained from rattan furniture workers in Ibadan, Oyo State, Nigeria. Three-layered boards of 6-mm thickness were made comprising coarse core and tine surfaces at two density levels of 1,050 kg/mi and 1,200 kg/m3, three CaCl2 concentration levels of: 2.5%, 3.0% and 3.5% and using Portland cement-cane mixing ratios of 2.5:l .0, 2.75: 1 .0, 3.0: 1 .0, and 3.25: 1 .0. After board manufacture, ASTM D 1037 (1998) test procedures were employed to obtain strength and moisture absorption properties. Average properties for bending modulus of rupture (MOR) and modulus of elasticity (MOE) of the boards ranged between 0.5 and 1.6 N/mm2, and 480 and 3,563 N/mrn2, respectively. Mean thickness swelling (TS) and water absorption (WA) values ranged between 1.1 and 8.6%, and 31 and 51%, respectively. Analysis of variance showed that except for MOE, the levels at which the density, CaCI2 concentration, and cement-cane mixing ratio were used and their interaction had no significant effects on properties of the board. The relatively low strength and water resistance properties of the boards make them suitable only for use in low stressed interior applications. Further investigations are, however, required on the effects of different cane preparation procedures and other fabrication variables on board properties. This is necessary to provide the guidelines required to adequately control the fabrication process and optimize material properties.